A 24-year record of high-frequency, in situ, observations of hydrogen at the Atmospheric Research Station at Mace Head, Ireland. (15th April 2019) - Derwent, Richard G.; Simmonds, Peter G.; O'Doherty, Simon J.; Manning, Alistair J.; Spain, T. Gerard
Abstract: Continuous high frequency in situ observations of hydrogen have been made at the Mace Head atmospheric research station on the Atlantic Ocean coastline of Ireland from April 1994 through to December 2017. These 40-minute observations represent one of the most comprehensive records of this trace gas carried out anywhere in the world. Hydrogen mixing ratios in northern hemisphere baseline air masses had a mean value of 508.81 ppb and exhibited a highly statistically significant upwards trend of +0.44 +0.16 -0.28 ppb year-1. Trends were strongest during the months of January, February and November and weakest during the months of May - July, inclusive. Monthly mean baseline mixing ratios exhibited a seasonal cycle with a spring maximum and an autumn minimum, the latter being relatively unusual at this baseline station. The transport of European regionally-polluted air masses to Mace Head historically brought elevated levels of hydrogen above baseline. Over the years of this study, these elevated levels have declined to the extent that the hydrogen levels in European regional pollution events are now almost indistinguishable from baseline levels. Photochemical Trajectory Model studies have confirmed that the decline in European excess hydrogen levels accurately reflects the widespread fitting of three-way catalysts and evaporative cannisters to petrol-engined motor vehicles across Europe and the reductions in emissions of carbon monoxide, oxides of nitrogen and volatile organic compounds that they have brought about. Highlights: Long-term baseline hydrogen level at Mace Head, Ireland averaged 508.81 ppb. Baseline hydrogen levels have shown an upwards trend of 0.4 ppb year −1 Hydrogen levels show a maximum in May and uniquely an October minimum.